A compact wideband dual‐polarized magnetoelectric dipole antenna. Issue 11 (2nd September 2022) - Li, Jie; Chen, Xing; Hao, Shu‐Ji; Cui, Yu‐Guo
Abstract: Magnetoelectric dipole antennas have attracted attention owing to their high performance, however, they are structurally complex and large. Attempts have been made to reduce their size, but the wideband properties and compact size are yet to be achieved simultaneously. This article proposes a dual‐polarized magnetoelectric dipole antenna to address these issues. The proposed antenna utilizes vertically oriented folded shorted patches to function as magnetic dipoles, which effectively enlarges the impedance bandwidth and stabilizes the antenna gain in the higher frequency. Additionally, it includes four L‐shaped metallic plates placed vertically on the reflector. Owing to the coupling with the adjacent electric dipoles, better impedance matching was obtained in the lower frequency, shifting the low limit of operating frequency to a lower frequency. This improvement enables the further enhancement of the impedance bandwidth and eventually a miniaturized structure is realized. A prototype was fabricated and measured with the results demonstrating that two ports both achieve 103% impedance bandwidth from 1.5 to 4.7 GHz, and the isolation was greater than 25 dB. Furthermore, stable radiation patterns with a gain of 7.1 ± 1.1 dBi was obtained. Moreover, the size of the antenna is very compact, which is only 0.37 λ L × 0.37 λ L × 0.11 λ L ( λ L denotes the wavelength at the lowest frequency).